Małżeństwo jako wspólnota i instytucja w nauce Kościoła katolickiego - Gębka, Mikołaj (Wydawnictwo Naukowe UAM, 2003)
The article presents an analysis of matrimony as a community and an institution in the doctrine of the Catholic Church. The issues of matrimony and family are very important for the Church. Over 40 official documents (letters, encyclicals, etc.) dealing with the problems of family and marriage have been published since the times of the Vatican Council II. Although the doctrine of family and marriage has been preached for over two thousand years in the Church, the last half of the century has brought significant intensification of research in the area. This is probably connected with the crisis of the traditional family model, as well as with the development of science. In the Catholic doctrine, matrimony has been mainly examined in its sacramental aspects; therefore it may turn out worthwhile to shed new light at the issue of marriage - to emphasize its communal and institutional aspects. From the point of view of the Church, matrimony is a deep community of life and love, established by the Creator and bound by a marital alliance (an irrevocable consent of both spouses). The community of the Holy Trinity is the model a married couple strives for. Marriage as an institution creates objective frames for the life of the spouses. According to the Church doctrine, matrimony is not purely a human institution, for God is its Creator and it is according to His will that a permanent institution is founded (it also remains permanent for the society). The Church lays great emphasis on the legalization of sexual life within marriage (a ‘justification’ in the eyes of God, the society and the spouse). The last part of the article presents an analysis of the sexual sphere of marriage with its institutional and communal features. It also shows a historical outline of how the two main goals of sexual life (procreation and the unification of the spouses) are interrelated. In conclusion, the Catholic conception of matrimony as an institution is a little different than the sociological one. The church emphasizes legalization and control, which are just one of many marital functions in the sociological depiction of marriage. When looking at marriage as a community - both attitudes are similar, though the Catholic view stresses the supportive role of God in the marital community
Matrimony as a community and an institution in the doctrine of the Catoholic Church